Optical response functions of ZnS, ZnSe, ZnTe by the LOM method - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
In recent years optical properties of nano-structures and semiconductors have gained increasing importance in many technological areas, such as blue laser fabrication techniques, optical switching devices, cascaded laser operations on chip sized platforms. In this work, the localized orbital method (LOM) is applied to compute the dielectric response functions for the semiconductors and the sample crystals of ZnS, ZnSe and ZnTe are taken into consideration. The bulk crystal response functions and atom-cavity optical responses are handled. This is the first application of LOM to optical properties of semiconductors. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: ZnS; ZnSe; ZnTe; cavities; response functions; local orbital method